2000
DOI: 10.1111/j.1469-7998.2000.tb00629.x
|View full text |Cite
|
Sign up to set email alerts
|

Sperm competition and genetic diversity in the agile antechinus (Dasyuridae: Antechinus agilis)

Abstract: The mouse-like marsupial Antechinus agilis is common to south-eastern Australia with breeding and lifehistory traits being highly synchronous. Mating activity is con®ned to a 10-to 15-day period in August, at the end of which all males die as a result of a stress-induced suppression of the immune system. Ovulation occurs at this time and females rely on stored sperm from specialized crypts in the lower isthmus of the oviduct for successful fertilization. Here we report a high incidence of mixed paternity litte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 30 publications
(89 reference statements)
1
12
0
Order By: Relevance
“…As males die before the young are born, paternal investment is limited to their genetic contribution. These male semelparous species tend to mate promiscuously, with factors such as genetic similarity (Parrott, Ward & Temple‐Smith, 2006), male genetic quality (Fisher et al ., 2006), mating order (Shimmin, Taggart & Temple‐Smith, 2000; Kraaijeveld‐Smit et al ., 2002) and male body size (Kraaijeveld‐Smit, Ward & Temple‐Smith, 2003) observed to affect siring success.…”
Section: Introductionmentioning
confidence: 99%
“…As males die before the young are born, paternal investment is limited to their genetic contribution. These male semelparous species tend to mate promiscuously, with factors such as genetic similarity (Parrott, Ward & Temple‐Smith, 2006), male genetic quality (Fisher et al ., 2006), mating order (Shimmin, Taggart & Temple‐Smith, 2000; Kraaijeveld‐Smit et al ., 2002) and male body size (Kraaijeveld‐Smit, Ward & Temple‐Smith, 2003) observed to affect siring success.…”
Section: Introductionmentioning
confidence: 99%
“…Mating in A. agilis is promiscuous and occurs in August. Multiple males usually contribute to the litters of 6 to 10 offspring, and male siring success is negatively associated with the genetic similarity between mates (Shimmin et al . 2000; Kraaijeveld‐Smit et al .…”
Section: Introductionmentioning
confidence: 99%
“…Previous work on sperm competition in A. agilis in captivity concluded that last‐male sperm precedence occurs, with the last male siring 64% of the offspring (Shimmin et al ., 2000). Last‐male precedence was strongest when both matings occurred early in the oestrous period, with the last male siring 72% (Shimmin et al ., 2000). Male size was not taken into account in this study, and the molecular technique used required that pouch young remain with the mothers until they were large enough to obtain sufficient DNA.…”
Section: Introductionmentioning
confidence: 99%
“…Male size was not taken into account in this study, and the molecular technique used required that pouch young remain with the mothers until they were large enough to obtain sufficient DNA. This resulted in reduced numbers of offspring, because when under stress, females may consume their own pouch young (Shimmin et al ., 2000). With current microsatellite typing techniques, only a small amount of tissue is needed for paternity analysis (Queller et al ., 1993), and paternity results can be obtained on complete litters, sampled immediately after birth.…”
Section: Introductionmentioning
confidence: 99%